2006
DOI: 10.1007/s00167-006-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic analysis in patients with multidirectional shoulder instability during pull, forward punch, elevation and overhead throw

Abstract: Multidirectional shoulder joint instability alters the role of dynamic stabilizers, as a result of which the motion patterns of the muscle around the shoulder joint are also changed. The aim of this study was to compare the muscle activity of patients with multidirectional shoulder instability and the control group during pull, forward punch, elevation and overhead throw. Fifteen subjects with multidirectional shoulder instability and fifteen control subjects with normal, healthy shoulders participated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 31 publications
1
28
0
2
Order By: Relevance
“…In addition, previous studies also observed changes in EMG activity in individuals with multidirectional instability during different isokinetic shoulder movements [4]. Particularly, it was found that EMG activity of the anterior AD, BIC and TrIC decreased while the EMG activity of the infraspinatus increased for the group with shoulder instability compared with a control group [4].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…In addition, previous studies also observed changes in EMG activity in individuals with multidirectional instability during different isokinetic shoulder movements [4]. Particularly, it was found that EMG activity of the anterior AD, BIC and TrIC decreased while the EMG activity of the infraspinatus increased for the group with shoulder instability compared with a control group [4].…”
Section: Discussionmentioning
confidence: 80%
“…In addition, previous studies also observed changes in EMG activity in individuals with multidirectional instability during different isokinetic shoulder movements [4]. Particularly, it was found that EMG activity of the anterior AD, BIC and TrIC decreased while the EMG activity of the infraspinatus increased for the group with shoulder instability compared with a control group [4]. In contrast, Barden et al [8] found no significant difference in EMG amplitudes during isotonic concentric/eccentric movements of the shoulder joint in individuals with multidirectional instability.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations